Pore-Level Study of Syngas Production From Fuel-Rich Partial Oxidation in a Simplified Two-Layer Burner - Shi, Junrui; Mao, Mingming; Li, Houping; Liu, Yongqi; Sun, Yasong (Frontiers in Chemistry, 2019)
We performed pore-level simulation of fuel-rich partial oxidation of a CO2/CH4 mixture in a two-dimensional porous burner with staggered arrangement of discrete particles. The chemistry was treated with detailed chemical kinetics GRI-Mech 1.2, and surface-to-surface radiation was taken into account by the discrete ordinates (DO) model. The predicted results were validated against the available experimental data and results by the volume-averaged method. The predicted main syngas products (CO, H2, and CO2) agreed well with the experimental data for the whole investigation range; it indicated that the pore-level simulation could precisely predict syngas productions from fuel-rich partial oxidation in a two-layer burner with the simplified arrangement of porous media. Variations of species, temperature, and velocity within the pores were presented and discussed. The predicted molar fractions of CO, H2, CO2, H2O, etc. over the pores between particles were highly two-dimensional; the flame thickness was on the order of the particle diameter (2.5 mm) and smaller than the particle diameter. The predicted area-weighted average temperatures were greater than the experiments due to the ignorance of the heat loss to the surroundings through burner walls. The effect of CO2 adding on syngas production is examined.